Comparative analysis of the in vitro cytotoxicity of the dietary biogenic amines tyramine and histamine. (15th April 2016) - Linares, Daniel M.; del Rio, Beatriz; Redruello, Begoña; Ladero, Victor; Martin, M. Cruz; Fernandez, Maria; Ruas-Madiedo, Patricia; Alvarez, Miguel A.
Highlights: In vitro cytotoxicity of histamine and tyramine was determined by RTCA. Both biogenic amines were cytotoxic at concentrations commonly found in certain foods. Tyramine showed a stronger and more rapid cytotoxic effect than histamine. Tyramine caused intestinal cell necrosis, while histamine induced apoptosis. Abstract: Tyramine and histamine, the most toxic biogenic amines (BA), are often found in high concentrations in certain foods. Prompted by the limited knowledge of BA toxicity, and increasing awareness of the risks associated with high intakes of dietary BA, the in vitro cytotoxicity of tyramine and histamine was investigated. Tyramine and histamine were toxic for HT29 intestinal cell cultures at concentrations commonly found in BA-rich food, as determined by real-time cell analysis. Surprisingly, tyramine had a stronger and more rapid cytotoxic effect than histamine. Their mode of action was also different, while tyramine caused cell necrosis, histamine induced apoptosis. To avoid health risks, the BA content of foods should be reduced and legal limits established for tyramine.